Eco-consciousness in Andrew Marvell’s The Garden - Joshi, Deepak (Far Western Review, 2024)
This paper explores ecological and environmental issues in Andrew Marvell’s poem, “The Garden.” The purpose of this paper is to subvert the anthropocentric world view by juxtaposing the Eco-centric world which provides ultimate pleasure to human beings. This paper employs qualitative and interpretative method to analyze the poem. The researcher has examined the poem from the perspective of Eco-criticism. Distancing himself from the anthropocentric world-view, Marvell highlights the Eco-centric world in order to valorize the beauty and serenity of nature. Marvell glorifies nature and natural beauty by using metaphysical conceits. The poem displays superiority of nature over trivial human culture. In addition, it shows eternity of nature by contrasting it with the transitory nature of human world. The garden is a place for refreshment and nourishment; it stands for innocence, solitude and recreation. Mistaken by the temptation of the material world, the poet seeks peace and pleasure in the human company. However; he finds such blissful states in the lap of nature. Marvell’s critique of anthropocentric and glorification of bio centrism opens an avenue for the critiques who are interested in integrating literary texts with the Environmental Studies. Thus; the present reading of the poem unveils the Eco-conscious elements of the poem from the lens of Eco-criticism.